Beyond Anxiety : Curiosity, Creativity, and Finding Your Life's Purpose - Beck, Martha Nibley, 1962- ([New York, New York] : Viking, an imprint of Penguin Random House LLC, 2025)
"Most of us assume that the key to overcoming [anxiety] is to think our way out. And for a while it works. But there is always something that sends us back into the anxious spiral we've been trying to climb out of. In [this book], Dr. Martha Beck explains why anxiety is skyrocketing around you, and likely within you. She also tells you how to not only reduce your anxiety but use it to propel you into a life filled with peace, meaning, and joy. Using a combination of the latest neuroscience as well as her background in sociology and coaching, Beck explains how our brains tend to get stuck in an 'anxiety spiral,' a feedback system that can increase anxiety indefinitely. To climb out, we must engage different parts of our nervous system--the parts involved in creativity"--
Keywords: Anxiety; Creative ability; Creation (Literary, artistic, etc.); Conduct of life; Emotions and feelings